1997
DOI: 10.1258/002367797780600279
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit haemorrhagic disease: the new scourge of Oryctolagus cuniculus

Abstract: A new, widespread and important disease of rabbits, rabbit haemorrhagic disease (RHD), is concisely reviewed and discussed. RHD is an acute, infectious condition of adult rabbits and morbidity and mortality, after a relatively short incubation period, can be very high. The disease appears typically as a necrotizing hepatitis with associated haemorrhaging, and death occurs as a result of generalized organ dysfunction. RHD is caused by a calicivirus, antigenically related to a similar virus found in brown hares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 63 publications
1
32
0
1
Order By: Relevance
“…W Europie liczne zachorowania, o nieznanej etiologii, królików hodowlanych, a później dzikich odnotowano w 1986 r. we Włoszech (13). W latach 1987-1989 choroba opanowała cały kontynent, a na początku lat 90. przeniknęła na Wyspy Brytyjskie (17). W Polsce choroba powszechnie znana jako pomór królików występuje od 1988 r. (31).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…W Europie liczne zachorowania, o nieznanej etiologii, królików hodowlanych, a później dzikich odnotowano w 1986 r. we Włoszech (13). W latach 1987-1989 choroba opanowała cały kontynent, a na początku lat 90. przeniknęła na Wyspy Brytyjskie (17). W Polsce choroba powszechnie znana jako pomór królików występuje od 1988 r. (31).…”
Section: Artykuł Przeglądowy Reviewunclassified
“…This is reminiscent of rabbit haemorrhagic disease virus (RHDV). Retrospective studies have shown that RHDV existed in rabbit populations for many years in a seemingly non-pathogenic form [9,11,70]. Then, in the 1980s, highly lethal forms were first reported in China, and have since appeared worldwide [58,72].…”
Section: Clinical Signsmentioning
confidence: 99%
“…RHD, an acute and highly contagious disease in wild and domestic rabbits (13,44), was first reported by Liu et al (30) in the People's Republic of China. The disease spread throughout Europe between 1987 and 1989 (37).…”
mentioning
confidence: 99%